Free-swimming fauna associated with influxes of pelagic sargassum: Implications for management and harvesting - Alleyne, Kristie S. T.; Small, Micaela; Corbin, Makeda; Vallès, Henri; Oxenford, Hazel A. (Frontiers in Marine Science, 2023)
Mass accumulations of pelagic sargassum (Sargassum natans and S. fluitans) in the Tropical Atlantic, across the Caribbean and off the coast of West Africa, are causing extensive ecological and socioeconomic harm. The extraordinary volumes of sargassum influxes could also provide a business opportunity if innovative ways are developed to utilise the raw material. In-water harvesting provides the best opportunity to collect substantial amounts of ‘fresh’ sargassum that can be used in a variety of applications. However, sargassum rafts are living and diverse ecosystems with a range of associated fauna including fish that are targeted by fishers. The consequences of in-water harvesting of sargassum on the biodiversity, including associated fishes, remain poorly understood. Characterisation of this biodiversity within nearshore and offshore environments is needed to help guide best harvest practices and assess possible impacts on fishing opportunities. We assessed the free-swimming fauna associated with sargassum rafts at various distances from shore with the use of underwater video recordings. Over a three-month period, a total of 35 underwater surveys were conducted off the eastern and southern coastline of Barbados. Thirteen species (12 fishes and one comb jelly) from 8 families were identified, with the family Carangidae representing the greatest number of species (n=6). Application of the MaxN metric (maximum number of individuals of a species seen during deployment) revealed significant correlations with raft characteristics notably raft volume, raft distance from shore and water depth. The three environmental variables accounted for 9% of the variation (adjusted R2) in the free-swimming community composition with raft volume being the major driver of species richness. This aligns with ecological theory and supports our hypothesis that larger rafts would host greater species richness. The results demonstrate a strong affiliation between pelagic sargassum rafts and species biodiversity and abundance that will need to be considered by managers when seeking a best compromise between protecting beaches from inundation by sargassum and protecting biodiversity and fishing opportunities.